2017
DOI: 10.1038/cddis.2017.218
|View full text |Cite
|
Sign up to set email alerts
|

DT-13 synergistically enhanced vinorelbine-mediated mitotic arrest through inhibition of FOXM1-BICD2 axis in non-small-cell lung cancer cells

Abstract: Non-small-cell lung cancer (NSCLC) is the most commonly diagnosed malignant disease with the leading cause of cancer-related death. Combination treatment remains the major strategy in the clinical therapy of NSCLC. Vinorelbine (NVB), a semi-synthetic vinca alkaloid, is used for advanced and metastatic NSCLC by destabilizing microtubule formation to induce mitotic arrest and cell death. However, the side effect of NVB heavily affected its effectiveness in clinical therapy. Hence, it is of great significance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Apoptosis involves a series of biochemical events that lead to a variety of morphological changes, including blebbing, changes to the cell membrane, cell shrinkage, nuclear fragmentation, chromatin condensation, and chromosomal DNA fragmentation [35]. In this study, an Annexin V-FITC/PI double staining method was used to evaluate the cell apoptosis after treatment with the varying liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis involves a series of biochemical events that lead to a variety of morphological changes, including blebbing, changes to the cell membrane, cell shrinkage, nuclear fragmentation, chromatin condensation, and chromosomal DNA fragmentation [35]. In this study, an Annexin V-FITC/PI double staining method was used to evaluate the cell apoptosis after treatment with the varying liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, natural medicines are often applied in combination with classical chemotherapy drugs to exert better therapeutic effects. 19 After screening combination treatment of JHC-4 with six common chemotherapy drugs, we found that the combination of JHC-4 with TAX exhibited the most remarkable synergistic effects based on different combination strategies (data are shown in Tables 1-6). Paclitaxel is a common drug for the treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, Chinese herbal medicine plays a vital role in cancer treatment, especially in enhancing efficacy and reducing toxicity when combined with chemical drugs. 18,19 But most of the mechanism of the increasing sensitivity is still confused. Interestingly, previous studies have reported that autophagy could potentiate sensitivity to chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, 5 × 10 3 cells were seeded onto the RTCA's E-96 plate. After 30 min of equilibrating, the plate was transport to RTCA and electrode resistance was recorded.Twenty-four hours later, cells were treated with siSPR and cultured for 8 h. After that, the media were changed and cell growth was monitored continuously up to another 72 h. MTT and colony formation assays were performed as previously described 28 . Apoptosis, cell cycle, and mitochondrial membrane potential were measured using annexin V-FITC apoptosis detection kit (Vazyme Biotech), Cell cycle and apoptosis analysis kit (Beyotime Biotechnology, Shanghai, China) or mitochondrial membrane potential assay kit (Beyotime Biotechnology) according to the manufacturer's instructions.…”
Section: In Vitro Functional Assaysmentioning
confidence: 99%